Hydrometallurgy of sulphide minerals with presence of bacteria in salinas - Lovera, Daniel (2008)
Mining is a productive activity based on the rational utilization of non-renewable natural resources. Avizorándose that many mining countries may not base its development with the extraction of raw materials, which must design new strategies for development. Mining has always been regarded as a positive scenario for the market, the strong global demand for metals (copper, zinc, nickel, iron and others), mainly generated by the dynamics of Asian countries –led mainly by China– have allowed have high values of prices never seen in history. The current investigation shows evidence of leaching minerals saline sulfur quite successfully it allows us to infer that the halophilic bacteria play an important role in the dissolution of minerals and could also be taken to account as bio-indicators in the environmental remediation work.